Effects of Manual Acupuncture Versus Sham Acupuncture in patients with Post-Stroke Depression: A Randomized Clinical Trial - Conghui Wei; Jinling Chen; Qu Yang; Jingjing Xu; Qingsong Li; Fulin Li; Yu Liu; Jun Luo (Neurology and Therapy)
Abstract Background Post-stroke depression (PSD) is a prevalent psychiatric complication in stroke patients, severely reducing quality of life and delaying social recovery in stroke survivors. Clinical studies have shown that acupuncture can be used as an alternative approach for PSD. The aim of this study was to examine the safety, efficacy, and electroencephalogram (EEG) mechanism of acupuncture in treating PSD patients. Methods From October 28, 2022 to May 16, 2023, this single-center, single-blind, randomized clinical trial was conducted at the Second Affiliated Hospital of Nanchang University. A total of 56 eligible subjects were assigned in a random manner, with an equal distribution between two groups: the manual acupuncture (MA) group and the sham acupuncture (SA) group. The primary outcome was the Hamilton Depression Scale-24 (HAMD-24); the secondary outcomes included the Pittsburgh Sleep Quality Index (PSQI), the National Institutes of Health Stroke Scale (NIHSS), the Barthel index, EEG power spectrum, and EEG imaginary coherent (iCOH). Results Compared to the SA group, the MA group exhibited significant improvements in HAMD-24, NIHSS, PSIQ, and Barthel index at week 6. The total improvement rate was 85.71% in the MA group and 28.57% in the SA group. After 6 weeks of treatment, the alpha and beta bands power spectrum increased significantly, while the delta and theta bands power spectrum decreased significantly in the MA group compared to the SA group. The iCOH analysis showed that the MA group had significantly higher functional connectivity in the four bands than the SA group. Conclusions Acupuncture might be regarded as an adjunctive treatment for PSD patients with improvements in their neurological deficits, sleep quality, and depression. Meanwhile, the mechanism of acupuncture in treating PSD patients may be through decreasing the slow wave power spectrum and increasing the fast wave power spectrum, and enhancing brain functional connectivity. Trial registration Chinese Clinical Trial Registry (ChiCTR2200065112/2022-10-28).